Let $a$, $b$, $c$, $d$ and $e$ be positive numbers. Prove that:


Easy to show that $$\frac{a}{a+b}+\frac{b}{b+c}+\frac{c}{c+a}\geq\frac{a+b+c}{a+b+c-\sqrt[3]{abc}}$$ is true

and for even $n$ and positives $a_i$ the following inequality is true.


  • $\begingroup$ hello Michael nice to meet you here i think BW! $\endgroup$ Nov 11 '14 at 18:02
  • $\begingroup$ Hello, Dr. Sonnhard Graubner! I think BW is not useable here. $\endgroup$ Nov 11 '14 at 20:31
  • $\begingroup$ The right side is never more than $n/2$. Can the left side be less than $n/2$? $\endgroup$
    – Paul
    Jan 23 '16 at 14:40
  • 3
    $\begingroup$ @Paul: For $(a, b, c, d, e) = (1, k, k^2, k^3, k^4)$ and $k \to \infty$, the lhs comes arbitrarity close to one. $\endgroup$
    – Martin R
    Jan 23 '16 at 22:06
  • $\begingroup$ @Michael: Can you share your "easy proof" for $n=3$ and $n$ even? $\endgroup$
    – Martin R
    Jan 24 '16 at 17:55

Here is a full proof.

Let us start the discussion for general $n$. Denote $S = \sum_{i=1}^n a_i$.

Since by AM-GM, $S \geq n \sqrt[n]{a_1a_2...a_n}$, we have

$$1+\frac{n(n-2)\sqrt[n]{a_1a_2...a_n}}{2S} \geq \frac{S}{S - (n-2)\sqrt[n]{a_1a_2...a_n}}$$

Hence a tighter claim is (simultaneously defining $L$ and $R$):

$$L = \sum_{cyc}\frac{a_i}{a_i+a_{i+1}}\geq 1+\frac{n(n-2)\sqrt[n]{a_1a_2...a_n}}{2S} = R$$ and it suffices to show that one.

We write $2 L \geq 2 R$ or $L \geq 2 R- L$ and add on both sides a term $$\sum_{cyc}\frac{a_{i+1}}{a_i+a_{i+1}}$$ which leaves us to show

$$n = \sum_{cyc}\frac{a_i + a_{i+1}}{a_i+a_{i+1}}\geq 2+\frac{n(n-2)\sqrt[n]{a_1a_2...a_n}}{S} + \sum_{cyc}\frac{-a_i + a_{i+1}}{a_i+a_{i+1}}$$ or, in our final equivalent reformulation of the L-R claim above, $$ \sum_{cyc}\frac{-a_i + a_{i+1}}{a_i+a_{i+1}} \leq (n - 2) (1- \frac{n \sqrt[n]{a_1a_2...a_n}}{S} )$$

For general odd $n$ see the remark at the bottom. Here the task is to show $n=5$.

Before doing so, we will first prove the following Lemma (required below), which is the above L-R-inequality for 3 variables (which is tighter than the original formulation, hence we cannot apply the proof for $n=3$ given above by Michael Rozenberg for the original formulation):

$$ \frac{b-a}{b+a} + \frac{c-b}{c+b} + \frac{a-c}{a+c} \leq (1- \frac{3 \sqrt[3]{a\, b \, c}}{a + b+ c} )$$

This Lemma is, from the above discussion, just a re-formulation of the claim in $L$ and $R$ above, for 3 variables, i.e.

$$ \frac{a}{b+a} + \frac{b}{c+b} + \frac{c}{a+c} \geq 1+\frac{3\sqrt[3]{a \, b \ c}}{2(a+b+c)}$$

By homogeneity, we can demand $abc=1$ and prove, under that restriction, $$ \frac{a}{b+a} + \frac{b}{c+b} + \frac{c}{a+c} \geq 1+\frac{3}{2(a+b+c)}$$

This reformulates into $$ \frac{a\; c}{a +b} + \frac{b\; a}{b +c} + \frac{c\; b}{c +a} \geq \frac{3}{2}$$ or equivalently, due to $abc=1$, $$ \frac{1}{b(a +b)} + \frac{1}{c(b +c)} + \frac{1}{a(c +a)} \geq \frac{3}{2}$$

which is known (2008 International Zhautykov Olympiad), for some proofs see here: http://artofproblemsolving.com/community/c6h183916p1010959 Hence the Lemma holds.

For $n=5$, we rewrite the LHS of our above final reformulation by adding and subtracting terms:

$$ \frac{b-a}{b+a} + \frac{c-b}{c+b} + \frac{d-c}{d+c} + \frac{e-d}{e+d} + \frac{a-e}{a+e} = \\ (\frac{b-a}{b+a} + \frac{c-b}{c+b} + \frac{a-c}{a+c}) + (\frac{c-a}{c+a}+\frac{d-c}{d+c} + \frac{a-d}{a+d}) + (\frac{d-a}{d+a}+ \frac{e-d}{e+d} + \frac{a-e}{a+e}) $$ This also holds for any cyclic shift in (abcde), so we can write

$$ 5 (\frac{b-a}{b+a} + \frac{c-b}{c+b} + \frac{d-c}{d+c} + \frac{e-d}{e+d} + \frac{a-e}{a+e}) = \\ \sum_{cyc (abcde)} (\frac{b-a}{b+a} + \frac{c-b}{c+b} + \frac{a-c}{a+c}) + \sum_{cyc (abcde)}(\frac{c-a}{c+a}+\frac{d-c}{d+c} + \frac{a-d}{a+d}) + \sum_{cyc (abcde)} (\frac{d-a}{d+a}+ \frac{e-d}{e+d} + \frac{a-e}{a+e}) $$

Using our Lemma, it suffices to show (with $S = a +b+c+d+e$)

$$ \sum_{cyc (abcde)} (1- \frac{3 \sqrt[3]{a\, b \, c}}{a + b+ c} ) + \sum_{cyc (abcde)}(1- \frac{3 \sqrt[3]{a\, c \, d}}{a + c+ d} ) + \sum_{cyc (abcde)}(1- \frac{3 \sqrt[3]{a\, d \, e}}{a + d+ e} ) \leq 15 (1- \frac{5 \sqrt[5]{a b c d e }}{S} ) $$ which is $$ \sum_{cyc (abcde)} (\frac{\sqrt[3]{a\, b \, c}}{a + b+ c} + \frac{\sqrt[3]{a\, c \, d}}{a + c+ d} + \frac{\sqrt[3]{a\, d \, e}}{a + d+ e} ) \geq 25 \frac{\sqrt[5]{a b c d e }}{S} $$ Using Cauchy-Schwarz leaves us with showing $$ \frac {(\sum_{cyc (abcde)} \sqrt[6]{a\, b \, c})^2}{\sum_{cyc (abcde)}(a + b+ c)} + \frac {(\sum_{cyc (abcde)} \sqrt[6]{a\, c \, d})^2}{\sum_{cyc (abcde)}(a + c+ d)} + \frac {(\sum_{cyc (abcde)} \sqrt[6]{a\, d \, e})^2}{\sum_{cyc (abcde)}(a + d+ e)} \geq 25 \frac{\sqrt[5]{a b c d e }}{S} $$ The denominators all equal $3S$, so this becomes $$ (\sum_{cyc (abcde)} \sqrt[6]{a\, b \, c})^2 + (\sum_{cyc (abcde)} \sqrt[6]{a\, c \, d})^2 + (\sum_{cyc (abcde)} \sqrt[6]{a\, d \, e})^2 \geq 75 \sqrt[5]{a b c d e } $$ Using AM-GM gives for the first term

$$ (\sum_{cyc (abcde)} \sqrt[6]{a\, b \, c})^2 \geq ( 5 (\prod_{cyc (abcde)} \sqrt[6]{a\, b \, c} )^{1/5})^2 = 25 (\prod_{cyc (abcde)} ({a\, b \, c} ) )^{1/15} = 25 \sqrt[5]{a b c d e } $$

By the same procedure, the second and the third term on the LHS are likewise greater or equal than $25 \sqrt[5]{a b c d e }$. This concludes the proof.


  1. the tighter $L-R$-claim used here is - for general $n$ - asked for in the problem given at Cyclic Inequality in n (at least 4) variables

  2. For general odd $n$, the above reformulation can be used again. For odd $n>5$, take the method of adding and subtracting terms to form smaller sub-sums which are cyclically closed in a smaller number of variables, and apply previous results for smaller $n$ recursively.

  • $\begingroup$ Beautiful proof. Thank you! $\endgroup$ Apr 29 '16 at 12:14
  • $\begingroup$ @Michael Rozenberg. Thank you for the bounty! In the original question you wrote "for even n and positives $a_i$ the following inequality is true." Could you make that solution available? $\endgroup$
    – Andreas
    Apr 29 '16 at 12:47
  • $\begingroup$ The proof for any $n$ (for the tighter L-R-claim stated above) is given here: math.stackexchange.com/questions/1711515 $\endgroup$
    – Andreas
    Apr 29 '16 at 18:33

A proof for $n=3$.

We'll prove that $\frac{a}{a+b}+\frac{b}{b+c}+\frac{c}{c+a}\geq\frac{a+b+c}{a+b+c-\sqrt[3]{abc}}$ for all positives $a$, $b$ and $c$.

Indeed, let $ab+ac+bc\geq(a+b+c)\sqrt[3]{abc}$.

Hence, by C-S $\sum\limits_{cyc}\frac{a}{a+b}\geq\frac{(a+b+c)^2}{\sum\limits_{cyc}(a^2+ab)}=\frac{1}{1-\frac{ab+ac+bc}{(a+b+c)^2}}\geq\frac{a+b+c}{a+b+c-\sqrt[3]{abc}}$.

Let $ab+ac+bc\leq(a+b+c)\sqrt[3]{abc}$.

Hence, by C-S $\sum\limits_{cyc}\frac{a}{a+b}\geq\frac{(ab+ac+bc)^2}{\sum\limits_{cyc}(a^2c^2+a^2bc)}=\frac{1}{1-\frac{abc(a+b+c)}{(ab+ac+bc)^2}}\geq\frac{1}{1-\frac{\sqrt[3]{abc}}{a+b+c}}=\frac{a+b+c}{a+b+c-\sqrt[3]{abc}}$.



A proof for even $n$.

Let $a_i>0$, $a_{n+1}=a_1$ and $n$ is an even natural number. Prove that: $$\frac{a_1}{a_1+a_2}+\frac{a_2}{a_2+a_3}+...+\frac{a_n}{a_n+a_1}\geq\frac{a_1+a_2+...+a_n}{a_1+a_2+...+a_n-(n-2)\sqrt[n]{a_1a_2...a_n}}$$ Proof.

By C-S and AM-GM $\sum\limits_{i=1}^n\frac{a_i}{a_i+a_{i+1}}=\sum\limits_{k=1}^{\frac{n}{2}}\frac{a_{2k-1}}{a_{2k-1}+a_{2k}}+\sum\limits_{k=1}^{\frac{n}{2}}\frac{a_{2k}}{a_{2k}+a_{2k+1}}\geq\frac{\left(\sum\limits_{k=1}^{\frac{n}{2}}\sqrt{a_{2k-1}}\right)^2}{a_1+a_2+...+a_n}+\frac{\left(\sum\limits_{k=1}^{\frac{n}{2}}\sqrt{a_{2k}}\right)^2}{a_1+a_2+...+a_n}\geq$


  • $\begingroup$ Thanks for the proof for even $n$ - very short and concise! $\endgroup$
    – Andreas
    Apr 29 '16 at 21:59

I'm going to prove a different but similar inequality.

Let $x_1,x_2,\ldots,x_n>0$, $x_{n+1}=x_1$, $x_{n+2}=x_2$, $n$ be a positive integer such that either

$a)\ $ $n\le 12$; or

$b)\ $ $13\le n\le 23$, $n$ is odd.

Then this inequality is true:

$$\sum_{i=1}^n\frac{x_i}{x_{i+1}+x_{i+2}}\ge \frac{\sum_{i=1}^n x_i}{\sum_{i=1}^n x_i - (n-2)\sqrt[n]{\prod_{i=1}^n x_i}}$$

Proof: by AM-GM:

$$\frac{\sum_{i=1}^n x_i}{\sum_{i=1}^n x_i - (n-2)\sqrt[n]{\prod_{i=1}^n x_i}}\le $$

$$\le \frac{\sum_{i=1}^n x_i}{\sum_{i=1}^n x_i - (n-2)\frac{\sum_{i=1}^n x_i}{n}}=$$

$$=\frac{\sum_{i=1}^n x_i}{\frac{2}{n}\sum_{i=1}^n x_i}=\frac{n}{2}$$

By Shapiro inequality: $$\frac{n}{2}\le \sum_{i=1}^n\frac{x_i}{x_{i+1}+x_{i+2}}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.